Geology and Characteristics of Pb-Zn-Cu-Ag Skarn Deposit at Ruwai, Lamandau Regency, Central Kalimantan - Idrus, Arifudin; Setijadji, L. D.; Thamba, F. (Geological Agency, 2011)
DOI: 10.17014/ijog.v6i4.126This study is dealing with geology and characteristics of mineralogy, geochemistry, and physicochemical conditions of hydrothermal fluid responsible for the formation of skarn Pb-Zn-Cu-Ag deposit at Ruwai, Lamandau Regency, Central Kalimantan. The formation of Ruwai skarn is genetically associated with calcareous rocks consisting of limestone and siltstone (derived from marl?) controlled by NNE-SSW-trending strike slip faults. It is localized along N 70° E-trending thrust fault, which also acts as the contact zone between sedimentary and volcanic rocks in the area. The Ruwai skarn is mineralogically characterized by prograde alteration comprising garnet (andradite) and clino-pyroxene (wollastonite), and retrograde alteration composed of epidote, chlorite, calcite, and sericite. Ore mineralization is typified by sphalerite, galena, and chalcopyrite, formed at early retrograde stage. Galena is typically enriched in silver up to 0.45 wt % and bismuth of about 1 wt %. No Ag-sulphides are identified within the ore body. Geochemically, SiO is enriched and CaO is depleted in limestone, consistent with silicic alteration (quartz and calc-silicate) and decarbonatization of the wallrock. The measured resources of the deposit are 2,297,185 tonnes at average grades of 14.98 % Zn, 6.44% Pb, 2.49 % Cu, and 370.87 g/t Ag. Ruwai skarn orebody was originated at moderate temperatures of 250 - 266 °C and low salinity of 0.3 - 0.5 wt.% NaCl eq. The late retrograde stage was formed at low temperature of 190 - 220 °C and low salinity of 0.35 wt.% NaCl eq., which was influenced by meteoric water incursion at the late stage of the Ruwai Pb-Zn-Cu-Ag skarn formation.